ELECTROPHYSIOLOGICAL AND NEUROCHEMICAL STUDIES OF THE MECHANISMS OF THE ANTICONVULSANT EFFECT OF THE NEW ORIGINAL COMPOUND GIZH-298 - S. A. Litvinova; T. A. Voronina; V. S. Kudrin; I. O. Gaydukov; L. N. Nerobkova; M. B. Pisclova; G. G. Avakyan; L. А. Zhmurenko (Эпилепсия и пароксизмальные состояния)
The aim of this study was to investigate the electrophysiological and neurochemical mechanisms of the anticonvulsant effect of a new original compound  GIZH-298 and to define the leading structure as the target for influence compound. Materials and  Methods. The partial (focal) and secondary generalized seizures were modeled by methods of creation a chronic epileptic focus  that was caused  by cobalt applique on the brain of rats. The liquid chromatography  (HPLC) analysis used for neurochemical study of the effect GIZH-298. There was studied the effect on metabolism  and quantity of biogenic amines in the brain structures of rats. Results. It was found that GIZH-298 at a dose of 60 mg / kg (i.p.) has a pronounced effect on the primary and especially secondary generalized epileptic foci in various brain structures with a primary influence on the cortex. GIZH-298 at a dose  of 60 mg / kg caused  a statistically significant increase in the content of serotonin and dopamine in the frontal cortex after 30 minutes after the administration and reduced the rate of metabolism  of dopamine  in the  dorsal striatum.  Conclusion.  The anticonvulsant  effect  GIZH-298  is enhanced  with increased of epileptic system, may be due to increased synthesis of serotonin and dopamine in the cortex, and decreased metabolism  of the latter in the striatum.